ZINC SUPPLEMENTATION IMPROVES REPRODUCTIVE PERFORMANCE OF KARAN-FRIES CATTLE - PATEL, B; KUMAR, N; JAIN, V; AJITHAKUMAR, H M; KUMAR, S; RAHEJA, N; LATHWAL, S S; DATT, C; SINGH, S V (The Indian Journal of Animal Reproduction, 2016)
The pregnant Karan-Fries (KF) cattle were either fed basal ration only (0Zn, n=6), or were daily supplemented with 80 and 120 ppm Zinc (Zn), respectively (80Zn or 120Zn, n=6 each) for 45 days before and after calving to assess their producing ability, parity and body weight. The number of cattle exhibiting retained fetal membranes and metritis were 2, 1 and 0 in 0Zn, 80Zn and 120Zn group, respectively. Moreover, compared to no Zn supplemented group, in 120Zn and 80Zn supplemented group, there was reduction (p
Keywords: Conception rate; Estrus; Karan Fries Cattle; Metritis; Zinc